Potensi Senyawa Fitokimia Ferulic Acid Turunan dari Senyawa Hydroxycinnamic Acid Derivatives Sebagai Antioksidan dengan Aktivitas Anti-Aging - Sofiana Hanifah Aprilia (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Human skin undergoes aging and degenerative processes, like other body tissues. Skin aging is characterized by various structural and functional changes, such as decreased skin elasticity, degradation of elastic fibers, thinning of the epidermis, reduced collagen content, the appearance of wrinkles, and increased skin dryness. One effort to inhibit this process is the use of natural phytochemical compounds with antioxidant and skin-protective activity, such as ferulic acid. Ferulic acid is known to scavenge free radicals and absorb ultraviolet (UV) light. Furthermore, this compound can protect the structure of collagen, elastin, and fibroblast cells from damage, and inhibit the enzymes collagenase and tyrosinase, which play a role in collagen degradation and the formation of hyperpigmentation. This literature review aims to examine the anti-aging activity of ferulic acid based on the results of in vitro and in vivo studies published in the past ten years. The search was conducted through a systematic literature review of relevant scientific articles. The results indicate that ferulic acid has a promising mechanism of action in preventing and slowing skin aging. This compound can improve skin elasticity, suppress melanin production, reduce dark spots, and exhibit anti-inflammatory properties that help reduce redness and inflammation caused by acne. Its antioxidant effects also contribute to slowing the appearance of wrinkles, thus helping maintain a more youthful appearance. Despite its significant potential, further research is needed to better understand its mechanism of action and long-term safety for use on human skin.